To the End: Exposing the Absolute - Ruda, Frank (Filozofski vestnik, 2020)
This article reconstructs Badiou’s oeuvre from the vantage point of the last volume of his Being and Event trilogy. It determines the perspective and task of The Immanence of Truths and demonstrates in what way an “absolute ontology” is the result of an act of forcing that serves as the measure for a truth’s truthness. This allows to argue that Badiou’s is and always was a philosophy of freedom.